Diffuse infantile hepatic hemangioma successfully treated with propranolol orally: a case report and literature review - Li, Zengyan; Wu, Zhiming; Dong, Youhong; Yuan, Xiaojun; Zhang, Dongdong (Frontiers in Oncology, 2024)
Background Infantile hepatic hemangioma (IHH) is a common vascular, fast-growing hepatic tumor that is usually accompanied by multiple cutaneous hemangiomas. Diffuse IHH (DIHH) is a rare type of IHH that exhibits many tumors with nearly complete hepatic parenchymal replacement. At present, there is no specific standardized treatment plan for DIHH. Herein, we present the case of a 2-month-old girl with DIHH and without cutaneous hemangioma who achieved complete remission after undergoing propranolol monotherapy. Case presentation The infant with low birth weight was presented to the pediatric department with a 2-month history of persistent vomiting and feeding difficulty. Ultrasonography and abdominal magnetic resonance imaging revealed hepatomegaly and diffused intrahepatic lesions. A computed tomography-guided percutaneous liver biopsy was performed, and the pathological examination suggested the diagnosis was DIHH. The patient exhibited remarkably response to an increasing dose of oral propranolol, from 0.5 mg/kg to 2 mg/kg every day. The intrahepatic lesions were almost completely regressed after one year of treatment and no distinct adverse reaction was observed. Conclusion DIHH can induce life-threatening complications that require prompt interventions. Propranolol monotherapy can be an effective and safe first-line treatment strategy for DIHH.